2015
DOI: 10.1080/03043797.2015.1095159
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy, mathematics’ anxiety and perceived importance: an empirical study with Portuguese engineering students

Abstract: The accomplishment in mathematics has gained attention from educators and arises as an emerging field of study, including in engineering education.However, in Portugal there is still incipient research in the area so it is high time to explore factors that might enlighten the gap in the study of the relationship between Portuguese engineering students and the learning of mathematics. The main purpose of this study is to explore three factors identified in the literature as influencing the learning of mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 35 publications
1
19
0
4
Order By: Relevance
“…In (Alves et al, 2016), the authors found that the Portuguese engineering students have rather high self-efficacy in mathematics and rate the importance of mathematics high. Consequently, they proposed a study focusing on the relationship between these measures and students' grades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In (Alves et al, 2016), the authors found that the Portuguese engineering students have rather high self-efficacy in mathematics and rate the importance of mathematics high. Consequently, they proposed a study focusing on the relationship between these measures and students' grades.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is naturally related to every study mentioned above but, especially, it can be seen as a complement to Bengmark et al (2017) and Alves et al (2016) as we are interested in the relations between the Swedish first-year engineering students' performance in mathematics, their views of mathematics, and their motivation and self-efficacy in mathematics.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This finding is worth acknowledging, since many previous studies suggest that female students' self-efficacy in mathematics is lower than that of male students (Sax et al 2015). There are also studies that associate mathematics anxiety with gender, so that female students suffer more anxiety dealing with mathematical tasks compared to male students (Alves et al 2016). The present results show that this may not be the case in every culture.…”
Section: Resultsmentioning
confidence: 88%
“…Further, they base on the self-determination theory by Ryan and Deci (2000). Alves et al (2016) collected data from a group of Portuguese undergraduate engineering students and examined the relationships between students' self-efficacy, mathematics anxiety (i.e. a tension that interferes with the manipulation of mathematical expressions and the solving of mathematical tasks), and the perceived importance of mathematics.…”
Section: Research Questionsmentioning
confidence: 99%
“…A number of them even expressed stern belief that their anxiety in language learning is worse than their anxiety in mathematics. This lends legitimacy in focusing also on anxiety towards learning in non-technical courses, whereas previous studies dealt with anxiety in traditionally engineering-related course, i.e., mathematics (Alves et al, 2016;Firouzian et al, 2015;Jamil et al, 2011;Leppävirta, 2011;Vitasari et al, 2010).…”
Section: Discussionmentioning
confidence: 99%